Transformational Leadership of Pucangsewu Village Head in Developing Sustainable Environmental Innovation - Senatama, Gandung; Choirunnisa, Luthfi Alif Dinar; Annshori, Muhammad Faqih; Zarasita, Jesika; Sari, Ekky Purnama; Harmansyah, Prianda Defri (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2025)
Environmental problems in Indonesia are increasingly disturbing with the varying amount of daily consumption of the community. Household waste is a serious problem in every region in Indonesia, including at the regional level. Innovation is needed in public services in the environmental sector to handle this case. Pucangsewu Village, Pacitan District, Pacitan Regency has designed a Recycling Center to process the waste of the Pucangsewu Village community. The purpose of this study will discuss a leader in the process of developing a local Recycling Center as a solution to the waste problem in the village. The theory used is Kharis' Transformational Leadership Theory (2015). This study uses a descriptive qualitative approach with an interview method. Researchers conducted interviews with actors who have roles in the innovation. The results of this study are that in its journey to develop the Pucangsewu Recycling Center, it experienced major obstacles, namely human resources who still do not know how to dispose of waste properly and in the process of sorting organic and inorganic waste. The impact of this study will provide knowledge and references for leaders to be more sensitive to environmental problems in their areas.